PRIVILEGING SPORT FOR ALL (Fiep Bulletin - online, 2012)
The Forum was attended by key personalities from the world of sports and physical education. They discussed topics related to sport and social integration, the international role of European sport and sport and media literacy. (Complete conclusions at: http://europa.eu.int/comm/sport)It has been scientifically proven that a physical (and sporting) activity that meets the individual?s abilities is beneficial in terms of health and improved quality of life. Sport is also a promoter of social integration among children and youngsters.In contrast to “sports for all”, which has numerous positive links with other social systems, extreme media coverage, excessive marketing and other factors created a separate social system known as Elite Sport. Despite offering potential educational effects, this kind of competitive sport is a privilege of particularly talented young people and adults. People who simply need to „exercise? are not interested in it.Therefore, it is necessary to change the sports policies, focusing on “sports for all” and promoting the integration of the minorities, including the physically and/or mentally disabled.Appeal for Fundamental Objectives- Education through sport must aim at improving personal performance and not top performance. Its mission consists in helping children to grow physically, intellectually and morally and to develop their personalities. It helps building self-confidence and self-esteem as well.- The “European Sport for All Charter”, launched in 1975 will allow all European citizens to practice the sport they choose in full freedom, without race, sex or age discrimination, at affordable costs.